Microsurgical Management of Trigeminal Schwannoma: Cohort Analysis and Systematic Review - Neves, Maick Willen Fernandes; de Aguiar, Paulo Henrique Pires; Belsuzarri, Telmo Augusto Barba; de Araujo, André Monteiro Soares; Paganelli, Samantha Lorena; Maldaun, Marcos Vinicius Calfat (Journal of Neurological Surgery Part B: Skull Base, 2019)
Background Trigeminal schwannomas are benign tumors with a predilection for women between 40 and 60 years of age and account for less than 0.5% of all intracranial tumors. Clinical presentation depends on size and location, and typical symptoms are ipsilateral hypesthesia, headache, and facial pain. Clinical features and imaging usually make the Diagnosis.Methods A retrospective cohort analysis of 14 patients treated at our institution between January 1999 and October 2016 was performed, with a critical and systematic review of data from the literature, focusing on articles published over the same period.Results Fourteen patients were included in our series comprised of mostly women with a mean age of 40 years. Lesion size ranged from 3 to 6.5 cm (mean 4.6 cm). Clinical status of patients was evaluated and also rated based on the Karnofsky Perfomance Scale with values greater than 90% found in all patients pre and postoperatively. Surgery was our treatment of choice, and gross total resection was achieved in 71% of patients. Associated morbidity was high at 57%, predominantly from cranial nerve palsy, and no deaths were encountered.Conclusions Microsurgery is a suitable treatment for large symptomatic trigeminal schwannomas, achieving good local control rates over the observation period at acceptable morbidity. Therefore, microsurgery appears to a suitable option. During the study period, a significant evolution in the availability of treatment methods occurred. Radiosurgery emerged as an alternative treatment for unresectable lesions. A comprehensive review of the available literature was performed, and results were compared according to treatment modality.
Keywords: brain tumor; trigeminal schwannoma; microsurgery; radiosurgery